High kinetic inductance cavity arrays for compact band engineering and topology-based disorder meters - Vincent Jouanny; Simone Frasca; Vera Jo Weibel; léo Peyruchat; Marco Scigliuzzo; Fabian Oppliger; Franco De Palma; Davide Sbroggiò; Guillaume Beaulieu; Oded Zilberberg; Pasquale Scarlino (Nature Communications)
Abstract Superconducting microwave metamaterials offer enormous potential for quantum optics and information science, enabling the development of advanced quantum technologies for sensing and amplification. In the context of circuit quantum electrodynamics, such metamaterials can be implemented as coupled cavity arrays (CCAs). In the continuous effort to miniaturize quantum devices for increasing scalability, minimizing the footprint of CCAs while preserving low disorder becomes paramount. In this work, we present a compact CCA architecture using superconducting NbN thin films manifesting high kinetic inductance. The latter enables high-impedance CCA (~1.5 kΩ), while reducing the resonator footprint. We demonstrate its versatility and scalability by engineering one-dimensional CCAs with up to 100 resonators and with structures that exhibit multiple bandgaps. Additionally, we quantitatively investigate disorder in the CCAs using symmetry-protected topological SSH edge modes, from which we extract a resonator frequency scattering of $$0.2{2}_{-0.03}^{+0.04}%$$ 0.2 2 − 0.03 + 0.04 % . Our platform opens up exciting prospects for analog quantum simulations of many-body physics with ultrastrongly coupled emitters.